Desenvolvimento de proposição tecnológica cuidativo-educacional com a equipe multiprofissional de uma unidade cirúrgica - Böck, Andressa (2019)
At the hospital level, there are profound and constant changes, with the growing and accelerated technological innovation, which makes available to health professionals and users, the most diverse types of technologies, where we highlight the care-educational technologies. The care-educational technologies are treated in this research as a set of scientific knowledge, which support the operationalization of the process of care and education of the other directly and indirectly in the practice of nurses, from everyday experience and research within a critical, reflexive, creative, transformative and multidimensional perspective between human beings and the environment in which they operate. The objective was to develop a proposal of Care-Educational Technology, based on the needs of the multi-professional team praxis of a general surgery unit of a University Hospital of Rio Grande do Sul. This is a methodological development study. The study was conducted at the General Surgery unit of a University Hospital (HU) reference for teaching, research, extension and assistance to the central region of the state of Rio Grande do Sul (RS). The participants of this study were 23 health professionals working in this unit. For the present study, an eight-step methodological script was developed, namely: reality diagnosis, theorizing, analysis and collective design of the technological proposal, theorizing and development, appreciation, final design, validation and evaluation. However, in this study, steps one through six were performed, the others will be performed in subsequent studies. Data collection was performed through non-participant observation and focus group, from February to October 2018. Data analysis and interpretation took place through Content Analysis. Ethical aspects were respected according to Resolution 466/2012. From the analysis of the testimonies and impressions, collected through the FGs and observations, two categories emerged, namely: the daily care-educational praxis of the multiprofessional health team; needs and possibilities for a care-educational technology proposition. The technological proposition developed in this study is aimed at the use of health professionals of the general surgery unit to assist in the orientation of patients / companions for hospital discharge. Its content addresses the aspects and care with the surgical wound and the main devices of use of patients during hospitalization and after discharge: tracheostomy, nasoenteral and nasogastric tubes, gastrostomy and jejunostomy, elimination ostomies, intermittent bladder catheterization at home, and delay catheter. The technological proposition is in electronic format, available on the computer system intranet of the University Hospital in which the research was developed. As a contribution, it is expected that this care-educational technological proposition, after its validation and evaluation, will be a facilitating instrument for guidance and information for patients / surgical companions about the preparation of hospital discharge and can be used as an ally in encouraging self care.